Characterization of nonlymphoid cells derived from rat peripheral lymph - Pugh, CW (The Rockefeller University Press, 1983)
Mesenteric lymphadenectomy in rats is followed by union of peripheral and central lymphatics, allowing the collection of intestine-derived peripheral lymph cells via the thoracic duct for several days. These cells include a proportion of nonlymphoid cells (NLC) that show irregular and heterogeneous surface morphology including long pseudopodia and veils. They stain variably for nonspecific esterase and acid phosphatase and are ATPase-positive. Their nuclei are irregular and some contain cytoplasmic inclusions, some of which show peroxidase activity and/or contain DNA. NLC have a range of densitites generally lower than that of lymphocytes. Freshly collected NLC express the leukocyte-common antigen (defined by monoclonal antibody MRC Ox 1) and Ia antigens (I-A and I-E subregion products defined by monoclonal antibodies) but they show a relative lack of other surface markers normally found on rat B or T lymphocytes (W3/13, W3/25, MRC Ox 12 (sIg), MRC Ox 19) or rat macrophages (FcR, C’R, mannose R, W3/25). In general NLC are only weakly adherent to glass or plastic. Although a subpopulation of NLC appear to have had a phagocytic past, freshly collected NLC fail to phagocytose a variety of test particles in vitro. NLC also appear incapable of pinocytosis in vitro. This heterogeneity may represent distinct subpopulations of NLC or different stages in the development of a single cell lineage. Direct cannulation of mesenteric lacteals shows that the majority of NLC are derived from the small intestine and their precursors appear to be present both in lamina propria and Peyer's patches. Kinetic studies, following irradiation or intravenous tritiated thymidine, show that the majority of NLC turn over rapidly in the intestine with a modal time of 3-5 d. Studies with bone marrow chimeras show that they are derived from a rapidly dividing precursor present in normal bone marrow. NLC occur at very low frequencies in normal thoracic duct lymph at all times following cannulation. The evidence presented suggests that NLC closely resemble mouse lymphoid dendritic cells. This conclusion is supported by evidence already obtained showing that NLC are potent stimulators of the semi-allogeneic rat primary mixed leukocyte reaction. In addition to the ceils resembling dendritic cells rare monocytoid cells are found in thoracic duct lymph of lymphadenectomized specific pathogen-free rats. The proportion of these cells increases greatly when the animals are conventionally housed. It seems probable that the physiological function of NLC is to act as accessory cells in the lymph nodes to which they normally drain. Methods for enriching NLC and thus facilitating analysis of their functions are discussed.